A trade-off between precopulatory and postcopulatory trait investment in male cetaceans. (1st June 2015) - Dines, James P.; Mesnick, Sarah L.; Ralls, Katherine; May-Collado, Laura; Agnarsson, Ingi; Dean, Matthew D.
Abstract: Mating with multiple partners is common across species, and understanding how individual males secure fertilization in the face of competition remains a fundamental goal of evolutionary biology. Game theory stipulates that males have a fixed budget for reproduction that can lead to a trade-off between investment in precopulatory traits such as body size, armaments, and ornaments, and postcopulatory traits such as testis size and spermatogenic efficiency. Recent theoretical and empirical studies have shown that if males can monopolize access to multiple females, they will invest disproportionately in precopulatory traits and less in postcopulatory traits. Using phylogenetically controlled comparative methods, we demonstrate that across 58 cetacean species with the most prominent sexual dimorphism in size, shape, teeth, tusks, and singing invest significantly less in relative testes mass. In support of theoretical predictions, these species tend to show evidence of male contests, suggesting there is opportunity for winners to monopolize access to multiple females. Our approach provides a robust dataset with which to make predictions about male mating strategies for the many cetacean species for which adequate behavioral observations do not exist.